Kebijakan Adopsi Nilai-Nilai Agama (Islam) dalam Pembaharuan Hukum Pidana Indonesia - Abdul Mutalib; Nur Azizah Rahman (Peneliti.net, 2020)
The first principle shows that Indonesia is a country that recognizes the existence of God, a religious state, a state that has criminal rules, which in practice should not have conflict with religious values ​​and laws adhered to by society. This research discusses the criminal provisions on offense of living together by not having married (zina) in the Criminal Code Bill (RUU KUHP), which is based on religious values ​​and criminal policies in the formulation of the Criminal Code. This research is intended to answer the problems regarding: what are the challenges, opportunities and formulation construction (ideas) in the policy of the Bill on the Criminal Code article 485 concerning about living together without being married (zina). The research method used is normative juridical method with qualitative analysis. The data analysis uses normative qualitative analysis by interpreting and constructing the statements contained in the Criminal Code Bill (RUU KUHP) which become positive legal norms. While qualitative, namely analyzing data that has the starting point of the discovery effort. The results of the study state that the current provisions of criminal acts of decency are not based on religious values.